Environmental education and school as an educational space to promote sustainability - Pedro César Cantú-Martínez (Revista Electrónica Educare)
This review paper discusses a topic of considerable importance for our society, which is environmental education and educational spaces, particularly when these elements are combined to achieve sustainability in society. The paper states that the current deterioration is guided by the countries’ urban and industrial progress and also indicates that it is in education, particularly in environmental education, and in educational spaces, where the medium will emerge to accommodate a social practice to achieve sustainable development.